A Growing Divide? Retirement Incomes by Gender in Australia - Keegan, Marcia; Harding, Ann; Kelly, Simon (My University, 2015)
Despite attempts to create a more equal environment for women and men, men in Australia continue to enjoy higher pay than women, particularly for those women who have had children. As the retirement of the baby boom cohort gathers pace, there has been much discussion about the extent to which these unequal changes during working life will translate into differences in well-being in retirement. This paper examines key differences in selected measures of well-being by gender in Australia, including a detailed analysis of trends in superannuation by age, gender and family type. The paper highlights the importance of the income unit used to examine these issues and discusses likely trends in the retirement income gap.
Keywords: Income & Finance -- Superannuation contribution; Gender -- Female; Employment -- Exit from employment (Retirement/Redundancy); Income & Finance -- Income inequality; Ageing; Income, wealth and finances; Labour market; Income & Finance; Gender; Employment; Income inequality; Superannuation contribution; Female; Exit from employment (Retirement/Redundancy); Income, wealth and finances; Employment and unemployment; Ageing